A Sociological Analysis of Education and Development In India: Exploring the Transformative Power of Education and Development in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In its broadest sense, education is a cultural process.This process transforms each new born infant from biological to social being.According to Spencer "education must conform to the natural process ofmental evolution-that there is a certain sequence in which the facultiesspontaneously develop, and certain kind of knowledge which each requires duringits development and supply this knowledge". While speaking on education hediscusses three different types of education i.e. intellectual, moral andphysical education. For him "in intellectual education the process ofself-development should be encouraged to the uttermost. Children should be ledto make their own investigation, and draw their own inferences.